Chyle Leak following Open Donor Nephrectomy: A Rare Complication—A Case Report - Sandeep Harkar; Dharam Vir Singh; Sanjay Kumar Gupta; Raghav Talwar; Yajvender Pratap Singh Rana (Case Reports in Transplantation)
Introduction. Donor workup in renal transplantation is extensive. Despite this, chyle leakage following donor nephrectomy, a rare complication, has been reported in the literature. We encountered two cases of chyle leak in kidney donors in our series of open donor nephrectomies. Summary of Cases. After complete workup, standard open retroperitoneal donor nephrectomy with drain placement was performed in 684 living renal donors. We encountered chyle leak in two cases. The first case was a 33-year-old female who underwent an otherwise uneventful left donor nephrectomy but continued to have high drain output (upto 300–400 mL/24 hrs) in the postoperative period. The drain fluid was milky, raising the suspicion of chyle which was confirmed on biochemical analysis. The second case was a 42-year-old female with a similar case history. Both were managed conservatively with low-fat diet. The leak subsided spontaneously in three weeks and one week in the first and second patients, respectively. The drain was removed, and the patients remained symptom-free on followup. Conclusions. Both of our cases of chyle leak following open donor nephrectomy were managed successfully with conservative management. The management options and the experience of other centers are reviewed and discussed.